Strategi Komunikasi Pemerintah Kota Baubau dalam Sosialisasi Nilai-nilai Kearifan Lokal - Suherman, Ansar; Mayunita, Sry; Mahyudin, Mahyudin; Yusuf, Ahmad (Tuturlogi: Journal of Southeast Asian Communication, 2020)
The communication strategy of the Baubau City Government in socializing the PO-5 program is a major problem in this study. The objective of this research is the concrete contribution of initial indicators to see the ability of the Baubau City government officials in the planning of the Communication Strategy and the selection of forms of communication media in the socialization process, as well as efforts to preserve the values of local wisdom in the lives of citizens and as a reference in an effort to preserve the values of local wisdom in the midst of society. The approach in this study uses the type of qualitative research with the following stages: the preparatory stage, the stage of composing the subject criteria, the Test and Revision Guidelines stage of the interview, the Data Collection stage, the data analysis stage, and the conclusion stage. The Baubau City Communication and Information Office is the agency that is responsible for developing strategies to socialize the PO-5 program to the Baubau community. The media used to socialize the program are stickers, billboards, banners, clothes, and advertisements in local newspapers. The findings in this study are the use of promotional media such as stickers, billboards, clothing, and advertisements in local newspapers are still the main choice in socializing the PO-5 program. Another finding was that socialization staffs were very minimal in terms of both quantity and quality in socialization activities so that the essence of the program was not yet understood by the majority of the community.